2014
DOI: 10.1111/aji.12248
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 and ERK1/2 Cross-talk in Leukaemia Inhibitory Factor Mediated Trophoblastic JEG-3 Cell Invasion and Expression of Mucin 1 and Fos

Abstract: ERK1/2 as well as JAK-STAT-mediated STAT3 (Ser727) phosphorylation play an important role in LIF-mediated JEG-3 trophoblastic cell invasion and gene expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…including Muc-1, through the janus kinase (JAK)/STAT3 and ERK1/2 signaling pathways (Suman & Gupta, 2014). Its suggested role in preventing implantation is consistent with its expression on the apical surface of the mouse LE, and its expression is timely downregulated before implantation (Surveyor et al, 1995).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…including Muc-1, through the janus kinase (JAK)/STAT3 and ERK1/2 signaling pathways (Suman & Gupta, 2014). Its suggested role in preventing implantation is consistent with its expression on the apical surface of the mouse LE, and its expression is timely downregulated before implantation (Surveyor et al, 1995).…”
Section: Discussionmentioning
confidence: 90%
“…LIF mRNA is expressed in both the endometrium and the blastocyst at the time of implantation, and its expression continues after the implantation for decidualization and the formation of the placenta (Nicola & Babon, ). Previous studies have also shown that in JEG‐3 cells, LIF induces changes in the expression of various genes involved in invasive cells, including Muc‐1, through the janus kinase (JAK)/STAT3 and ERK1/2 signaling pathways (Suman & Gupta, ). Its suggested role in preventing implantation is consistent with its expression on the apical surface of the mouse LE, and its expression is timely downregulated before implantation (Surveyor et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Prolactin is perhaps best known for its role in lactation [32]; however, it is also responsible for activating several other pathways such as the JAK-STAT pathway, including STAT3 [33, 34]. The function of STAT3 is well established in pregnancy, including involvement with embryonic implantation [35, 36], angiogenesis [37], and parturition [38, 39]. …”
Section: Discussionmentioning
confidence: 99%
“…The role of gp130 cytokines in trophoblast cells has been most extensively reviewed elsewhere and hence only briefly discussed here. IL‐6 and LIF stimulate the invasion of primary trophoblast and JEG‐3 choriocarcinoma cells; the involvement of IL‐11 is less clear. IL‐11 inhibits the invasion of primary trophoblast and HTR‐8/SVneo cells, but increases the invasion of the choriocarcinoma JEG‐3 cells and stimualtes migration of EVTs …”
Section: Pro‐invasive Factorsmentioning
confidence: 99%